Ticks and associated pathogens collected from cats in Sicily and Calabria (Italy) - Pennisi, Maria-Grazia (Parasit Vectors, 2015)
BACKGROUND: Limited information is available about the species of ticks infesting the cat and the pathogens that they harbor. The aims of the present study were to identify the species of ticks removed from cats living in Sicily and Calabria (Italy) and to detect DNA of vector-borne pathogens in the same ticks. FINDINGS: Morphological identification of 132 adult ticks collected throughout the year from cats was carried out. Real-time PCRs for Hepatozoon felis, Piroplasmid, Ehrlichia/Anaplasma spp., Rickettsia spp., Bartonella spp., Mycoplasma spp. and Leishmania infantum were performed from each individual tick. Ticks belonging to Rhipicephalus (R. sanguineus sensu lato, R. pusillus) and Ixodes (I. ricinus, I. ventalloi) genera were identified. Ixodes ventalloi was the most frequently found tick species (47 %). The positivity rate to at least one pathogen was 14.4 % (19/132 ticks). Leishmania infantum, Rickettsia spp. (R. monacensis and R. helvetica), Bartonella spp. (B. clarridgeiae), Piroplasmid (Babesia vogeli), and Ehrlichia/Anaplasma spp. (E. canis) DNAs were amplified in 8.3, 5.3, 1.5, 0.75 and 0.75 % of ticks, respectively. Hepatozoon felis, Anaplasma spp. and hemotropic Mycoplasma spp. DNAs were not detected. Four (21.1 %) out of nineteen positive ticks were co-infected. CONCLUSIONS: This study provides novel data about ticks infesting cats and the DNA of pathogens that they harbor. In Southern Italy, anti-tick prophylaxis should be implemented throughout the year in cats without neglecting winter time.